Use of Idarucizumab to Revert the Anticoagulant Effect of Dabigatran in Heart Transplant Surgery: An Institutional Experience - Álvaro Herrera-Escandón; Orlando Castaño-Cifuentes; Carlos A. Plata-Mosquera (Case Reports in Cardiology)
Heart transplant is a surgical procedure with a high risk of perioperative bleeding in patients with a previous history of sternotomy, congestive liver disease, and/or use of oral anticoagulants. Anticoagulation is usually done with coumarin agents (warfarin, acenocoumarol), while on the waiting list, vitamin K is available allowing for partial reversal of the anticoagulant effect, although with variable INR and risk of uncontrolled bleeding. Direct oral anticoagulants have emerged as an alternative to the use of coumarins in patients with nonvalvular atrial fibrillation (NVAF). The main disadvantage of this group of drugs is that there was no specific reversal agent available that would allow an urgent reversal of the anticoagulant effect. The recent commercialization of idarucizumab (specific reversal agent) has allowed patients with NVAF on the waiting list for heart transplant to be treated with dabigatran. We present the case of a patient with advanced chronic heart failure and NVAF anticoagulated with dabigatran, who underwent urgent heart transplant after administration of idarucizumab, without complications derived from its use or from anticoagulation.